Bloodstream infection and pneumonia caused by Chlamydia abortus infection in China: a case report - Changjun Zhu; Minjie Lv; Jianling Huang; Changwen Zhang; Lixu Xie; Tianming Gao; Bo Han; Wenjing Wang; Ganzhu Feng (BMC Infectious Diseases, 2022)
Abstract Background Chlamydia abortus is generally considered to cause abortion, stillbirth, and gestational sepsis in pregnant women, but it’s rare in bloodstream infection and pneumonia. Case presentation We present details of a patient with bloodstream infection and pneumonia caused by Chlamydia abortus. Both blood next-generation sequencing (NGS) and sputum NGS indicate Chlamydia abortus infection. The patient received intravenous infusion of piperacillin sodium and tazobactam sodium (4.5 g/8 h) and moxifloxacin (0.4 g/d) and oral oseltamivir (75 mg/day). Within one month of follow-up, the patient's clinical symptoms were significantly improved, and all laboratory parameters showed no marked abnormality. However, chest computer tomography (CT) showed the inflammation wasn’t completely absorbed. And we are still following up. Conclusions Chlamydia abortus can cause pneumonia in humans. NGS has the particular advantage of quickly and accurately identifying the infection of such rare pathogens. Pneumonia is generally not life-threatening, and has a good prognosis with appropriate treatment. However, Chlamydia infection can lead to serious visceral complications which clinicians should pay attention to.